Formulation of Basic Assumptions Pesantren Entity Accounting - Binti, Binti Shofiatul Jannah; Iwan Triyuwono; Zaki Baridwan; Bambang Hariadi (The International Journal of Accounting and Business Society, 2025)
ABSTRACT Purpose — The research objectives are, first, to criticize the use of entity theory, which is the basis for the development of accounting for Islamic organizations (pesantren). It suggests that absolute property rights are in the individual, so the form of accounting favours the interests of the owner of capital (capitalist). Second, to formulate basic assumptions of the pesantren entity accounting. Design/methodology/approach—This research uses a qualitative research approach. We conducted a literature study to criticize the entity theory. We then conducted semi-structured interviews with two clerics (ulama) who are administrators of pesantren. All interviews were recorded with a tape recorder and then transcribed. Furthermore, data analysis refers to Miles et al. (2018), namely data condensation, data display, drawing, and verifying conclusions. Findings—Pesantren's assets must be separated from those of the owner (kiai). Furthermore, Pesantren’s assets are managed by Nadzir, who takes into account profits for the maslahah. Thus, Allah SWT owns the Pesantren assets, while Nadzir is only the manager. The basic assumptions of the Pesantren entity go beyond materialism and secularism. Practical implications—The basic concept of pesantren entities differs from that of business entities. The pesantren entity admits to the afterlife, while the business entity only exists in this world. We hope that the results of this research can impact the entity assumptions in the conceptual framework. Originality/value — This research develops a new concept of pesantren entities that differ from business entities. The pesantren entity concept represents the characteristics of the pesantren environment, the oldest educational institution in Indonesia. Keywords — Entity Theory; Pesantren; Waqf Assets. Paper type — Conceptual paper